The Psychological Characteristics and Job Satisfaction in Relation to The Happy Workplace of Electrical Industrial Factory Personnel in Pathumthani Province. - Chantabul , Phongthawach (International Journal of Membrane Science and Technology, 2023)
The objectives of this research aimed to study 1) the level of significance of psychological characteristics, job satisfaction and happy workplace of electrical industrial factory personnel in Pathumthani Province. 2) To study the relationship between psychological characteristics and happy workplace of electrical industrial factory personnel in Pathumthani Province. 3) To study the relationship between psychological characteristics and job satisfaction of electrical industrial factory personnel in Pathumthani Province. 4) To study the relationship between job satisfaction and happy workplace of electrical industrial factory personnel in Pathumthani Province. The population is the personnel from a total of 191 electrical industrial factories in Pathumthani Province. Using Taro Yamane’s formula, 35 electrical industrial factories were selected to be calculated with unknown population sample size. A sample of 385 personnel with 11 production personnel were purposive sampled from each factory. Statistical tool was questionnaire, and statistics used for analysis were frequency, percentage, mean and Pearson’s correlation coefficient. The research had found that: 1) The overall level of significance of psychological characteristics, job satisfaction and happy workplace was found that in general the level of importance was high at average of 3.67, when considered individually, it was found that the highest aspect was happy workplace at average of 3.74, followed by job satisfaction at average of 3.71, and psychological characteristics at average of 3.57. 2) The relationship between psychological characteristics and happy workplace of electrical industrial factory personnel in Pathumtani Province had a high positive correlation (r = .972, Sig <.05). 3) The relationship between psychological characteristics and job satisfaction among electrical plant personnel in Pathumtani Province and electrical industrial factory personnel in Pathumtani Province had a high positive correlation (r = .771, Sig <.05). 4) The relationship between job satisfaction and happy workplace among electrical plant personnel in Pathumthani Province and electrical industrial factory personnel in Pathumtani Province had a high positive correlation (r = .843, Sig <.05).